Fronts at the Surface Ocean Can Shape Distinct Regions of Microbial Activity and Community Assemblages Down to the Bathypelagic Zone: The Azores Front as a Case Study - Baltar, Federico; Arístegui, Javier (Frontiers in Marine Science, 2017)
Oceanic fronts are widespread features which separate distinct water masses. They are well known to control the distribution of microbial communities in surface waters, although there is scarce information on their role in delimiting critical functions that microbes perform, and on whether their effects can be translated down into the dark ocean. Here we carried out the first study on the variability of hydrolysis of organic matter (extracellular enzymatic activities; EEA) across a permanent front (the Azores Front), coupled with changes in microbial assemblage composition, from the surface down to the bathypelagic zone. The front separated the study area (enclosed into the North Atlantic Subtropical Gyral Province) into two distinct latitudinal sub-regions with sharp differences in the abundance of autotrophic and heterotrophic microbial assemblages, as well as in the extracellular enzymes activities of glucosidases, alkaline phosphatase and leucine aminopeptidase. South of the front there was an abrupt decline in the abundance of picophytoplankton as well as in heterotrophic prokaryotes with high nucleic-acid content, but an increase in the abundance of prokaryotes with high side-scatter, an indication that cells were growing attached to particles. Concomitantly, there was also an increase in the aminopeptidase to glucosidase ratio, a proxy of higher degradation of proteinaceous material relative to carbohydrates. Interestingly, these sharp changes in microbial assemblages and enzymatic activities north and south of the front were translated down to the deep ocean. Our results suggest that permanent fronts, like the Azores Front, can act as ecological boundaries in the ocean (even within a biogeographical province), in terms of microbial community structure and biogeochemical cycling. Oriented studies on oceanic fronts down to the deep ocean will help to understand how the variability of these widely-extended hydrographic futures will impact microbial communities and carbon cycling in a future ocean affected by trends in global warming, de-oxygenation and acidification.